Palladium-Catalyzed Asymmetric Quaternary Stereocenter Formation - Gottumukkala, Aditya L.; Matcha, Kiran; Lutz, Martin; de Vries , Johannes G.; Minnaard, Adriaan J. (Chemistry : a European journal, 2012)
An efficient palladium catalyst is presented for the formation of benzylic quaternary stereocenters by conjugate addition of arylboronic acids to a variety of β,β‐disubstituted carbocyclic, heterocyclic, and acyclic enones. The catalyst is readily prepared from PdCl2, PhBOX, and AgSbF6, and provides products in up to 99 % enantiomeric excess, with good yields. Based on this strategy, (−)‐α‐cuparenone has been prepared in only two steps. Jack of all trades: An efficient Pd catalyst for the formation of benzylic quaternary stereocenters by conjugate addition of arylboronic acids to a variety of β,β‐disubstituted cyclic and acyclic enones is presented (see scheme). The catalyst provides product enantioselectivities up to 99 %.